2020
DOI: 10.1021/acs.analchem.0c01429
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Deterioration State of Archaeological Wooden Artifacts: A Nondestructive Protocol based on Direct Analysis in Real Time – Mass Spectrometry (DART-MS) Coupled to Chemometrics

Abstract: Evaluating the deterioration state of archeological wood is obligatory before the preservation of archeological wooden artifacts. Herein, a nondestructive, accurate, and rapid methodology is first developed via direct analysis in real time-mass spectrometry (DART-MS) with chemometrics to classify archeological wood and recent wood into 3 groups according to their deterioration states. As water in wooden artifacts probably affected the ion fragmentation process during DART-MS, ions responsible for evaluating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Dong et al utilized TD‐DART‐MS to classify Cannabis hemp cultivars with principal component analysis (PCA) and partial least squares discriminant analysis (PLS‐DA) models. In addition, DART‐MS coupled to chemometrics was also applied to achieve the nondestructive evaluation of the deterioration state of archeological wooden artifacts, and the analysis time was only 0.7 min per sample (Guo et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
“…Dong et al utilized TD‐DART‐MS to classify Cannabis hemp cultivars with principal component analysis (PCA) and partial least squares discriminant analysis (PLS‐DA) models. In addition, DART‐MS coupled to chemometrics was also applied to achieve the nondestructive evaluation of the deterioration state of archeological wooden artifacts, and the analysis time was only 0.7 min per sample (Guo et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
“…Atmospheric pressure ionization MS 22,23 attracts considerable attention due to its easy sample pretreatment in identifying mixtures. To a certain degree, the emergence of desorption electrospray ionization (DESI) 24 and direct analysis in real time (DART) 25 demonstrated the possibility of ionizing and sampling analytes directly from the sample surface.…”
Section: Introductionmentioning
confidence: 99%
“…V. Deklerck et al 26 studied DART-MS in combination with a random forest as a powerful tool for wood species identification. Yin et al 22 published a paper in which they described that DART-MS took 0.7 min for each wooden artifact and could accurately predict the inhomogeneous deterioration states of archeological wooden artifacts when coupled to chemometrics. Apart from that, desorption atmospheric pressure chemical ionization mass spectrometry (DAPCI-MS) was applied for the differential analysis of untreated camphor wood products with sufficient sensitivity and high throughput, allowing a confident differentiation of camphor wood products from other wood samples within 3 min.…”
Section: Introductionmentioning
confidence: 99%
“…Adams proposed structures for the principal peaks arising from the DART-TOFMS analysis of lignin in an article about the analysis of printing and writing papers [20]. Guo et al detected lignin peaks by DART mass spectrometry in an evaluation of the deterioration state of archaeological wooden artifacts [21]. Crawford et al compared DART and spray ionization methods for lignin analysis mass spectrometry and concluded that spray methods produce more high-mass species than DART [22].…”
Section: Introductionmentioning
confidence: 99%